The effect of TGF-β1 and β-estradiol on glycosaminoglycan and type II collagen distribution in articular chondrocyte cultures - Abdul Rahim, S.; Selvaratnam, L.; Kamarul, Tunku (2008)
Articular cartilage extracellular matrix (ECM) plays a crucial role in regulating chondrocyte functions via cell—matrix interaction, cytoskeletal organization and integrin‐mediated signaling. Factors such as interleukins, basic fibroblast growth factor (bFGF), bone morphogenic proteins (BMPs) and insulin‐like growth factor (IGF) have been shown to modulate the synthesis of extracellular matrix in vitro. However, the effects of TGF‐β1 and β‐estradiol in ECM regulation require further investigation, although there have been suggestions that these factors do play a positive role. To establish the role of these factors on chondrocytes derived from articular joints, a study was conducted to investigate the effects of TGF‐β1 and β‐estradiol on glycosaminoglycan secretion and type II collagen distribution (two major component of cartilage ECM in vivo). Thus, chondrocyte cultures initiated from rabbit articular cartilage were treated with 10 ng/ml of TGF‐β1, 10 nM of β‐estradiol or with a combination of both factors. Sulphated glycosaminoglycan (GAG) and type II collagen levels were then measured in both these culture systems. The results revealed that the synthesis of GAG and type II collagen was shown to be enhanced in the TGF‐β1 treated cultures. This increase was also noted when TGF‐β1 and β‐estradiol were both used as culture supplements. However, β‐estradiol alone did not appear to affect GAG or type II collagen deposition. There was also no difference between the amount of collagen type II and GAG being expressed when chondrocyte cultures were treated with TGF‐β1 when compared with cultures treated with combined factors. From this, we conclude that although TGF‐β1 appears to stimulate chondrocyte ECM synthesis, β‐estradiol fails to produce similar effects. The findings of this study confirm that contrary to previous claims, β‐estradiol has little or no effect on chondrocyte ECM synthesis. Furthermore, the use of TGF‐β1 may be useful in future studies looking into biological mechanisms by which ECM synthesis in chondrocyte cultures can be augmented, particularly for clinical application.